Effect of a System Air Conditioner on Local Air Quality in a Four-bed Ward - Jungsuk Lee; Jung-Hun Noh; Kwang-Chul Noh; Young-Won Kim; Se-Jin Yook (Aerosol and Air Quality Research)
Abstract In a ward where many patients are hospitalized, effective ventilation is important because airborne viruses may cause secondary infection. This study investigates the changes in the air quality in a four-bed ward according to the use of a ventilation system (VS), an air cleaner (AC), a system air conditioner (SAC), and personal curtains. The age of air was obtained both experimentally and numerically, and used as an indicator for the ventilation efficiency assessment. Consequently, the air flows from the outlets of the four-way cassette SAC could interfere with or contribute to the introduction of fresh air depending on the positions in the ward. For positions where the fresh air could not reach easily when only the VS was used, the air quality was improved by the additional use of the SAC. While the use of personal curtains prepared for each bed interfered with the air flow in the ward and resulted in local spots with poor air quality, the operation of both the VS and the SAC enhanced the air flow and improved the local air quality. The overall indoor air quality was improved when the AC was used. However, the ventilation efficiency was reduced when the SAC was operated along with the AC, and the air quality deteriorated at positions where the flow caused by the SAC and that by the AC interfered with each other.